2015
DOI: 10.1002/jaba.226
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of resistance to change with unconditioned and conditioned reinforcers

Abstract: Several reinforcer-related variables influence a response's resistance to change (Nevin, 1974). Reinforcer type (i.e., conditioned or unconditioned) is a reinforcer-related variable that has not been studied with humans but may have clinical implications. In Experiment 1, we identified unconditioned and conditioned reinforcers of equal preference. In Experiments 2, 3, and 4, we reinforced participants' behavior during a baseline phase using a multiple variable-interval (VI) 30-s VI 30-s schedule with either co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 44 publications
(41 reference statements)
0
11
1
1
Order By: Relevance
“…The current results differ somewhat from those found by Vargo and Ringdahl (; Experiment 4). In their study with four typically developing preschoolers, these authors found that presession access to edible items had a more deleterious effect on responding maintained by token reinforcement than responding maintained by edible reinforcement.…”
Section: Discussioncontrasting
confidence: 99%
“…The current results differ somewhat from those found by Vargo and Ringdahl (; Experiment 4). In their study with four typically developing preschoolers, these authors found that presession access to edible items had a more deleterious effect on responding maintained by token reinforcement than responding maintained by edible reinforcement.…”
Section: Discussioncontrasting
confidence: 99%
“…It is perhaps assumed that all reinforcers would function equally in the context. However, previous research has demonstrated that differences may emerge in similar experimental arrangements under conditions of primary versus conditioned reinforcement (Leon et al, ; Vargo & Ringdahl, ).…”
Section: Discussionmentioning
confidence: 98%
“…Além dos reforços automáticos, outra relação de grande importância no ambiente clínico, por exemplo, são os reforços incondicionados. Vargo e Ringdahl (2015) investigaram e compararam a resistência à mudança de comportamentos mantidos por reforços condicionados e incondicionados em quatro experimentos, com crianças com desenvolvimento típico. No Experimento 1, identificaram-se reforçadores condicionados e incondicionados de igual preferência.…”
Section: C1unclassified